Ag2S nanoparticle-decorated MoS2 for enhanced electrocatalytic and photoelectrocatalytic activity in water splitting. Issue 2 (14th December 2016) - Wang, Min; Ju, Peng; Li, Wen; Zhao, Yun; Han, Xiuxun
Abstract : Tight nanojunctions between Ag2 S and MoS2 were constructed, which facilitates the separation of photogenerated charge carriers. Abstract : In this article, a novel Ag2 S nanoparticle-decorated MoS2 composite (A@M) was synthesized through a facile in situ growth of the monoclinic crystallographic Ag2 S on MoS2 nanosheets. The A@M composite was used as a catalyst in water splitting which exhibits higher electrocatalytic and photoelectrocatalytic activity than the respective pure MoS2 and Ag2 S counterparts. Experimental results indicate that the as-prepared A@M composite with an optimal Ag2 S/MoS2 molar ratio of 16.30% (16%A@M) shows the best catalytic performance with low overpotentials (110 mV for V oc, 190 mV for onset overpotential, 208 mV for the current density of 20 mA cm −2 ), a small Tafel slope (42 mV dec −1 ), and a high photocurrent (82 μA cm −2 under an applied potential of 0.4 V). The enhanced electrocatalytic activity is associated with the improved electrical conductivity resulting from the stretched MoS2 nanosheets and the enriched active sites due to the decorated Ag2 S particles. The formation of a type II heterojunction structure at the interface between Ag2 S and MoS2 facilitates the separation of photogenerated charge carriers, and thus is responsible for the enhanced photoelectrocatalytic activity and photocatalytic H2 production rate (628 μmol h −1 g −1 ). This work suggests a promising choice to overcome the intrinsic drawbacks of MoS2 nanostructures for the application in hydrogen evolution.